Innovation in Education: Improving the Quality of Learning in The Digital Era - Chrystie, Della; Putri, Setiani (Indonesian Journal Publisher, 2025)
Digital technology has significantly influenced education, particularly in learning methods, media, and systems. Educational innovation is essential to meet the demands of the 21st century, emphasizing flexibility, information access, and relevant skills. Innovations not only involve new technologies but also curriculum updates, pedagogical approaches, and the evolving role of teachers as facilitators. Blended learning models and the use of interactive tools like Google Classroom, Quizizz, Wordwall, and Kahoot have improved student engagement and motivation. Platforms like SPADA have helped equalize access to quality education across Indonesia. However, challenges persist, such as digital inequality, limited infrastructure, lack of teacher training, and resistance to change. Negative effects of technology overuse, including social disconnection and moral decline, also need attention. Thus, educational innovation must be balanced with character development, digital literacy, and collaboration among schools, families, and government. With structured strategies, education in the digital era can foster a creative, critical, and globally competitive generation.